Dory's Paradoxical Characterizations in Disney's Animated Feature Film Finding Dory (2016) (Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
The appearance of Dory, the forgetful blue tang fish, as the main character in Finding Dory (2016), one of Disney’s animated feature films, makes the film popular and has been nominated to 46 awards and won 16 awards. Previously, Dory was a helping character in the original film, Finding Nemo (2003). This study aimed to identify Dory’s characterizations by using textual analysis to find the uniqueness of Dory in the film. The analysis resulted in Dory’s paradoxical characterization where she was forgetful yet creative, reliant yet independent, and anxious yet confident. These paradoxes implied that this film portrays that negative characters can be developed into good characters. Therefore, this film can be used as media to develop characters in informal education.